The Effectiveness of Cognitive Counseling with Cognitive Restructuring Techniques to Increase Students' Interest in Literacy - Peni Aprilia Ningsih; Ni Ketut Suarni; I Ketut Dharsana (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The lack of students’ literacy is required to be overcome in order to create well-informed and active human sources so it required an effective counselling technique. As a response of this current phenomenon, this research aimed at determining the effectiveness of Cognitive Counselling Theory with Cognitive Restructuring Techniques to Increase Students' Interest in Literacy. The type of quasi-experimental research is non-equivalent control group design with pre-test and post-test control group design. The involvement of students of class X, totalling 39 people as the experimental class and 39 as the control class were selected as the sample of this research. The data analysis method used is the t-test using the SPSS 20.0 Windows 10 program. The results of the t-count data analysis are evident from the t-hit value of 10,733 > 0,227 t-table. So that Ho is rejected and Ha is accepted. The conclusion of this investigation was cognitive counselling with cognitive restructuring techniques is effectively used to increase literacy interest in SMA Negeri 2 Singaraja students. The implication of this study is on the change of the students cognitive and for the counsellor who wants to implement a new effective technique.